Atividade da Euterpe oleracea mart sobre os fatores de virulência de Aspergillus fumigatus em superfície abiótica e celular - BORGES, Katia Regina Assunção (2019)
Introduction. Euterpe oleracea Mart. provides several health benefits with various biological activities like anticancer, anti-inflammatory, antioxidant and antimicrobial. Objectives. To evaluate the activity of extract and oil of E. oleracea Mart. on virulence factors two strains of Aspergillus fumigatus on abiotic surface and cellular. Methodology. 360g of total fruit were crushed in a grinder and placed in 400ml of ethyl alcohol PA, which was macerated for 10 days and stirred for 2hs / day, then rotoevaporated and lyophilized. Seeds of Euterpe oleracea Mart were scraped and crushed for oil extraction by the Soxhlet system. Cytotoxicity and antifungal activity of extract and oil were evaluated in lung fibroblast cell and Aspergillus fumigatus strains. Fragments of drainage, urinary catheter and nasogastric catheter were submitted to the test of adherence to the formation of biofilm by placing them in a tube with 0.85% saline without culture medium. The adherence and biofilm of A. fumigatus in GM07492A normal lung fibroblast cells was evaluated at times of 3, 6, 12 and 24 h. Later, in the tests, the fragments were washed 3x with sterile distilled water, stained with violet crystal (CV) placed in a tube with 3ml of saline passed in the Vortex for 5 ', then the count of conidia adhered was counted in Neubauer chamber and culture for counting colonies. Colonized cells were stained by panoptic dye and analyzed by light microscopy. Results. The crude oil of Euterpe oleracea Mart semen is rich in lauric acid, oleic acid, linoleic acid, palmitic acid and myristic acid. Extract and oil were not cytotoxic to GM07492A cell, but have been shown to have antifungal properties for A. fumigatus strains. Extract and oil presented a stripping property on the adhesion and biofilm formed by the strains of A. fumigatus on the abiotic surface. Conclusion: It is suggested that the extract and the oil of the seed are two Euterpe oleracea Mart products with antibiobilis properties and with low cytotoxicity for normal cells, besides having antifungal activity.